417. Comparative Assessment of Multiple SARS-CoV-2 Antibody and Neutralization Assays from Blood Samples in COVID-19 Infected Patients. (31st December 2020) - Dewar, Robin L; Trevino, Christina; Lallemand, Perrine; Highbarger, Helene; Elbeik, Tarek A; Rehman, Tauseef; Holbrook, Michael; Schmaljohn, Connie; Lane, Cliff; Chary, Aarthi; Holodniy, Mark
Abstract: Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2, COVID-19) has caused a world-wide pandemic. Diagnosis is usually made by an RT-PCR test from a respiratory sample. A number of tests are available for antibody detection or assessment, including rapid, enzyme immunoassays (EIA) and neutralization. However, characterization of the antibody immune response is not well documented and the clinical significance of COVID antibodies remains largely unknown. In addition, comparison of results across different assay formats using identical samples has not been rigorously studied, making clinical interpretation of serologic tests difficult. Assessment of multiple SARS-CoV-2 antibody and neutralization assays from blood samples in COVID-19 infected patients Methods: 1–5 serial (total 33) serum or plasma samples from 14 patients who were positive for SARS-CoV-2 by EUA authorized RT-PCR assays from nasopharyngeal specimens where tested with the following COVID-19 antibody tests: LFA rapid tests (Chembio DPP IgM/IgG, SD Biosensor Standard IgM/IgG, BTNX Rapid Response IgM/IgG), and EIA tests (BioRad Platelia SARS-CoV-2 Total antibody-IgG/IgM/IgA, EuroImmun SARS-CoV-2 IgG, and EuroImmun SARS-CoV-2 IgA). See Table 1 for results and EUA. Results were recorded as positive, negative, or equivocal. Additionally, antibody neutralization was assessed on matched samples. Results: Mean age of SARS-CoV-2 positive patients was 73 years (range 65–89), 11/14 had symptoms, all were male and hospitalized (6 ICU), and 3 died. Average number of days serum was collected after RT-PCR positivity was 13.5 days (range -3 to 46 d). BTNX assay was only tested on 16 samples. Among all assays, total concordance of results was 91%. When only IgG/IgM or total antibody assays were considered, concordance of results was 96% (Table). IgA specific results were discordant in 9/33 (27%) of samples compared to other assays. Two patients were negative in all assays in serial samples collected within one week of PCR positivity. Antibody neutralization was detected, but not from all samples. Conclusion: In general, there was good agreement among antibody detection assays. Neutralization may reflect disease outcome. The study was limited by the number of positive samples and patient number, and at the time specificity was not addressed for all the assays. Disclosures: All Authors : No reported disclosures